Learning Organization, Strategy Adoption and Knowledge Transfer as Factors for Improving Performance of Higher Education Institutions: A Literature Review - Habtoor, Ammar S. (UUM Press, 2018)
Learning organization plays an important role in improving organizational performance. It is well-known from various sectors that this variable plays a significant role in enhancing the performance of various organizations and is used for promoting effective competitive advantage. Although there are many studies in this area of management, very few studies are available on Higher Education Institutions (HEIs). The objective of this study is to review the literature on learning organization and its relationship with organizational performance. In addition, the study reviews the literature on strategy adoption and knowledge transfer as they are also ascribed to the improvement of organizational performance. Hence, there are relationships between strategy adoption and knowledge transfer and organizational performance. Finally, the study makes a conclusion based on previous studies on the relationship among the variables and recommends that empirical studies use moderating and mediating variables between learning organization and organizational performance improvement in the HEI setting.